2007
DOI: 10.1007/s00595-006-3408-1
|View full text |Cite
|
Sign up to set email alerts
|

A Placebo-Controlled Comparison of Bupivacaine and Ropivacaine Instillation for Preventing Postoperative Pain After Laparoscopic Cholecystectomy

Abstract: We herein showed that the intraperitoneal instillation of local anesthetic during laparoscopic cholecystectomy is a noninvasive, rapid, safe and simple analgesic technique that reduces the total morphine consumption during first 24 h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
55
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 28 publications
10
55
0
Order By: Relevance
“…Our results confirm literature findings about analgesic effects of intraperitoneal ropivacaine instillation in VC surgeries [6][7][8]10,11 . In our study, patients receiving intraperitoneal 150mg of 0.5% ropivacaine at surgery completion, had significant decrease in abdominal pain scores up to two postoperative hours and time for first rescue analgesia was longer as compared to patients receiving 0.9% saline solution instillation.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results confirm literature findings about analgesic effects of intraperitoneal ropivacaine instillation in VC surgeries [6][7][8]10,11 . In our study, patients receiving intraperitoneal 150mg of 0.5% ropivacaine at surgery completion, had significant decrease in abdominal pain scores up to two postoperative hours and time for first rescue analgesia was longer as compared to patients receiving 0.9% saline solution instillation.…”
Section: Discussionsupporting
confidence: 91%
“…These authors have obtained morphine consumption decrease in all time intervals evaluated in the first 24h, while in our study there has been decrease only at emergence and in total consumption. This difference might be due to several factors present in the study 10 , among them the use of epinephrine which might have delayed local anesthetic absorption; the different multimodal analgesia (fentanyl at anesthetic induction and sodium diclofenac after intubation) and opioid administration via PCA. PCA is the ideal method to adequately administer opioids and measure their consumption, as compared to the administration of analgesics according to demand by a trained team, as performed in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Kucuk et al suggested that ropivacaine at adequate dose (150 mg) is significantly more effective than bupivacaine and low dose ropivacaine (100 mg). 13 The mean dose of ropivacaine used in our study was well tolerated and had no secondary effect. Ropivacaine as local anaesthetic has low toxicity and longer duration of action.…”
mentioning
confidence: 73%
“…It reaches a peak within the first few hours following the operation but diminishes with time. [6][7][8][9] The origin of pain after laparoscopic cholecystectomy is multifactorial with pain arising from the incision sites (somatic pain), from the gallbladder bed (visceral pain) and as a consequence of a pneumoperitoneum. Though the pain scores were less in pre-emptive group.…”
Section: Discussionmentioning
confidence: 99%